(untitled) (Archives of Pediatrics of Uruguay, 2023)
The nutritional approach of the very low birth weight infant poses a great challenge to most neonatologists in their clinical practice, and it is frequently delayed until de newborn is in stable clinical conditions. Currently, scientific evidence supports that early nutritional optimization impacts directly on this group’s survival and on their survival without major morbidities. Initiatives fostering early breastfeeding should be prioritized by the healthcare team. Quality improvement has shown to be a very useful resource to improve outcomes regarding neonatal mortality and morbidities.